b1+b3=15
b2+b4=30
S10=?
b1*(1 - q^n)
S10 =
q - n
b1+b3=15
b2+b4=30
b2=b1*q
b3=b1*q²
b4=b1*q³
b1+b1*q² =15
b1*q + b1*q³=30
b1(1+q²)=15
b1(q+q³)=30
Поделим 2 на 1
b1(q+q³) 30
=
b1(1+q²) 15
q + q³ q (1 + q²)
= 2 = 2
1 + q² 1 + q²
q = 2
b1(1+q²) =15
b1(1+ 2²)=15
5b1 = 15
b1 = 3
3 * (1 - 2^10) 3 * (1 - 1024)
S10 = =
1 - 2 -1
S10 = 3 * 1023 = 3069
S10 = 3069
Пошаговое объяснение:
1) (6+2)*5 = 8*5 = 40
2) 6*5 + 2*5 = 30 + 10 = 40
1) (3+4)*2 = 7*2 = 14
2) 3*2 + 4*2 = 6 + 8 = 14
1) (6+4)*3 = 10*3 = 30
2) 6*3 + 4*3 = 18 + 12 = 30